Nursing protects honeybee larvae from secondary metabolites of pollen. Issue 1875 (21st March 2018) - Lucchetti, Matteo A.; Kilchenmann, Verena; Glauser, Gaetan; Praz, Christophe; Kast, Christina
Abstract : The pollen of many plants contains toxic secondary compounds, sometimes in concentrations higher than those found in the flowers or leaves. The ecological significance of these compounds remains unclear, and their impact on bees is largely unexplored. Here, we studied the impact of pyrrolizidine alkaloids (PAs) found in the pollen of Echium vulgare on honeybee adults and larvae. Echimidine, a PA present in E. vulgare pollen, was isolated and added to the honeybee diets in order to perform toxicity bioassays. While adult bees showed relatively high tolerance to PAs, larvae were much more sensitive. In contrast to other bees, the honeybee larval diet typically contains only traces of pollen and consists predominantly of hypopharyngeal and mandibular secretions produced by nurse bees, which feed on large quantities of pollen-containing bee bread. We quantified the transfer of PAs to nursing secretions produced by bees that had previously consumed bee bread supplemented with PAs. The PA concentration in these secretions was reduced by three orders of magnitude as compared to the PA content in the nurse diet and was well below the toxicity threshold for larvae. Our results suggest that larval nursing protects honeybee larvae from the toxic effect of secondary metabolites of pollen.